Children's strategy choices and discoveries: Testing predictions of SCADS in multiplication - Pavlin-Bernardić, Nina (2010)
When solving arithmetical problems, children choose strategies in an adaptive manner. They also frequently discover new strategies. Shrager and Siegler (1998) developed Strategy Choice and Discovery Simulation (SCADS), which explains how children discover new addition strategies and select from among them. The aim of this study was to examine the applicability of SCADS to the domain of multiplication. To test different aspects of the model, we have carried out a research with children and developed a computer simulation for the solving of multiplication problems. The participants were 82 second-grade primary school children to which the multiplication problems were presented three times during the six-month period. The children's answers were audio recorded and two raters classified independently the strategy use. Computer simulation was developed according to SCADS, for the domain of multiplication. It included associative and metacognitive learning mechanisms. The results of simulation were compared to children's results. The simulation produced the same changes as children did in response latencies, frequency of errors and adaptiveness in strategy choices. However, it did not discover all of the multiplication strategies used by the children, since it was not possible to discover all of these strategies by recombining the operators from the existing strategies, which the model proposes for addition. Because of that, we suggested some additions to the model and compared simulation's results thus obtained to children's results. The results were very similar, which supports the expanded model.
Projekt MZOS
ENG